1991
DOI: 10.1111/j.1600-051x.1991.tb01698.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a plaque control programme on the incidence and severity of cyclosporin‐induced gingival changes

Abstract: The efficacy of plaque control as a means of preventing cyclosporin-induced gingival overgrowth was assessed in 27 adult renal transplant patients. After baseline examination, patients were randomly allocated to receive intensive oral hygiene instructions, scaling and root planing (OH group) or no treatment (no treatment group). Gingival condition was assessed 6 months after baseline and changes in gingival form were related to various periodontal and pharmacokinetic measures. In both treatment groups, there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
123
0
19

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(150 citation statements)
references
References 15 publications
8
123
0
19
Order By: Relevance
“…Abundant plaque (PI ≥ 2 in 40% of the sites) was associated with a 5.4 times higher risk of GO. 3 However, according to Seymour and Smith, 7 optimal plaque control is insufficient to prevent GO. Our results showed low mean PI (0.88) and GI (0.84) values, and did not reveal any association between these parameters and the occurrence of GO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abundant plaque (PI ≥ 2 in 40% of the sites) was associated with a 5.4 times higher risk of GO. 3 However, according to Seymour and Smith, 7 optimal plaque control is insufficient to prevent GO. Our results showed low mean PI (0.88) and GI (0.84) values, and did not reveal any association between these parameters and the occurrence of GO.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have studied the etiology of GO in patients receiving kidney transplant surgery and immunosuppressive treatment. Studies have evaluated the association of GO with bacterial plaque, 7 periodontal disease, treatment dosage and duration, plasma concentrations, 5 concurrent use of calcium channel blockers (CCBs), 8 and genetic susceptibility. 9 Greenberg et al 3 recently studied a sample of 115 patients that underwent kidney transplants and found a GO prevalence of 53% among those who were treated with CsA.…”
Section: Introductionmentioning
confidence: 99%
“…Si bien es aceptada su relación directa con fármacos y el factor genético, entre otros, el rol del biofilm bacteriano (placa dental) ha sido controvertido [5][6][7][8][9] .…”
Section: Gingival Enlargement Can Be An Adverse Effect Of Ciclosporinunclassified
“…Similarly, gingival hyperplasia is a common complication of posttransplant medication regimens, especially when they include cyclosporin A (CsA) and calcium channel blockers (209). In a small, randomized, controlled trial, posttransplant plaque control with intensive oral hygiene instruction, scaling and root planing had a beneficial effect on CsA-associated gingival hyperplasia (210). It has also been shown that pretrans- It is likely that influenza is more severe when it occurs in immunosuppressed renal transplant recipients (Table 30), although systematic studies documenting this are lacking.…”
Section: Rationalementioning
confidence: 99%